LGG-05. SINGLE CELL RNA SEQUENCING REVEALS MITOGENIC AND PROGENITOR GENE PROGRAMS IN BRAF-REARRANGED PILOCYTIC ASTROCYTOMAS. (23rd April 2019) - Reitman, Zachary; Paolella, Brenton; Bergthold, Guillaume; Pelton, Kristine; Becker, Sarah; Jones, Robert; Sinai, Claire; Malkin, Hayley; Huang, Ying; Grimmet, Leslie; Herbert, Zachary; Sun, Yu; et al.
Abstract: Pilocytic astrocytoma (PA) is the most common pediatric low-grade glioma. While PAs exhibit a favorable prognosis compared to higher-grade gliomas, treatment morbidity and tumor recurrence still represent major challenges for some PA patients. PAs frequently harbor rearrangements resulting in expression of oncogenic KIAA1549-BRAF fusion transcripts. We performed scRNAseq of both tumor and non-tumor cells in newly-diagnosed PAs that contained KIAA1549-BRAF rearrangements. To confidently distinguish tumor cells from nontumor cells, we sorted cells by glial progenitor marker A2B5 status and profiled KIAA1549-BRAF fusion status of cells using a quantitative PCR-based assay. Results were validated using RNA in situ hybridization and compared to bulk expression data from 151 pediatric low grade gliomas. When compared to higher-grade gliomas, a higher proportion of the PA tumor cells exhibited a differentiated, astrocyte-like phenotype. A smaller proportion of cells exhibited a progenitor-like phenotype with evidence of proliferation. These progenitor-like tumor cells expressed a mitogen-activated protein kinase (MAPK) gene program that was absent from higher-grade gliomas. Similar patterns of expression of genes associated with the astrocyte-like and MAPK gene programs were also seen in formalin fixed, paraffin embedded PA tissues using RNA in situ hybridization. Immune cells, especially microglia, comprised almost half of all cells in the PAs and accounted for many differences seen in bulk pediatric low grade glioma expression profiles. These single cell transcriptional data reveal a transcriptional developmental hierarchy in a pediatric low-grade glioma that is skewed towards more mature brain cells compared to higher-grade gliomas. The results indicate that future analyses of bulk PA tissues should attempt to account for considerable infiltration by nontumor cells. Finally, the finding that a MAPK gene program is not uniformly expressed in PA tumor cells has implications for ongoing clinical investigations of therapies directed at the MAPK pathway for the treatment of PA.